ANALISIS PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI, REAL ESTATE DAN KONSTRUKSI BANGUNAN - Amna Mawardi (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of company growth, capital structure, and dividend policy on firm value in property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the period 2013-2017. The data used are secondary data and the method used is panel data regression analysis with the help of the Eviews 9 program to obtain a comprehensive picture of the relationship between one variable with another variable. The sample in this study consisted of 19 companies that were consistently listed on the IDX for 5 years in the 2013-2017 period with purposive sampling as a sampling method. The results of this study are that the variable capital structure and dividend policy have a significant influence on the firm's value partially at a level of significance of less than 5%. While the company's growth variable does not have a significant effect on the company's value partially. The results of the simultaneous regression analysis found that company growth, capital structure, and dividend policy together affect the value of the company. The predictive ability of the three variables on firm value is 72.1% while the remaining 27.9% is influenced by other factors